Milankovitch Cycles, New Insights - Jovanović, Gordana (European Journal of Applied Sciences, 2024)
Milutin Milankovitch published his influential research “Canon of Insolation and the Ice-age Problem” in Belgrade, Serbia, in 1941. His work is still significant in terms of studying climate changes. In this paper we also consider new scientific knowledge about solar insolation. Periodic solar activities such as sunspots and the magnetic field cycles or grand solar minimum/maximum affect the Earth’s atmosphere. These periodic natural factors, together with Milankovitch cycles, are important for regional and for global climate.